ch41-p050 - 50. According to Eq. 41-6, P ( E F + E ) =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
50. According to Eq. 41-6, PE E ee e F EE E k T E k T x FF () / / += + = + = + +− ∆∆ 1 1 1 1 1 1 where x E kT =∆ / . Also, E e F E k T E k T x . / / + = + = + −− 1 1 1 1 1 1 Thus, E E xx ( ) . ++ −= + + + = + = 1 1 1 1 11 1 A special case of this general result can be found in Problem 41-6, where
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 05/19/2011 for the course PHY 2049 taught by Professor Any during the Spring '08 term at University of Florida.

Ask a homework question - tutors are online